Incrementar el rendimiento en las excavadoras cat 336dl reduciendo los tiempos improductivos en mejora de la producción de relleno masivo en Minera Tahoe Perú la Arena S.A - Asuncion Gomez, Gianmarco (2019)
The present research work was carried out in the Unit Minera Tahoe Perú la Arena S.A. whose objective is to increase the performance in CAT 336dl excavators by reducing downtime in improving the production of the massive landfill. In these first months of July August and September we were faced with problems such as the excess queues of the hauling equipment on the loading fronts and in the unloading areas. Being cargo one of our main activities to meet the required production per mine and one of the most significant operations together with the haulage, we seek to increase it in improving the company. Carrying out the studies in the loading activities, the most significant were the presence of delays, non-operational and operational, they present a problem for our operational KPIs, the low use of our equipment affects their productivity and performance, not allowing Achieve compliance with our monthly production. For this, we carried out the study of the identification of downtimes and operational losses in loading activities. For this purpose, we generated controls that help us to standardize and maintain the continuous improvement in each of the activities, by reducing the downtimes you can obtain a use high and therefore an acceptable productivity based on the unit operating costs in the cargo, analyzing the production reports that arrived from the operators it was noted that the increase in operational delays were the most significant during the operation, this due to certain factors by which such delays occur such as slope profiling, tail in discharges and loading, fuel supply, guard delivery, operator training, etc. Our excavator performance increased from 436.7 Tn / hr to 522.83 Tn / hr, in addition to obtaining other results such as a reduction of $ 0.152 / tn to $ 0.127 / tn in unit costs, the use of the excavators increased from 74.88% to 83.39%.